THE USE OF MEDIATION AS AN ALTERNATIVE DISPUTE RESOLUTION IN THE RESOLUTION OF INTELLECTUAL PROPERTY RIGHTS DISPUTES - Sabela Gayo (International Asia Of Law and Money Laundering, 2022)
In the world of digitization where human ability in business has penetrated into the virtual world, the development of this business needs legal protection of intellectual property is growing very rapidly. Various forms of dispute resolution in the field of intellectual property are then present in supporting the creation of legal protection of intellectual property rights holders in Indonesia. The exclusive rights of these creators, inventors and designers are often abused without rights by others for personal gain. This journal aims to determine the arrangement of dispute resolution in the field of intellectual property and to determine the forms of mediation that can be chosen or used in the resolution of intellectual property disputes. The writing of this journal uses normative legal research methods. The results showed that the arrangement of dispute resolution in court was made by filing a civil lawsuit in the Commercial Court and conducting criminal prosecution in the General Court. Arbitration may also be chosen as a medium for resolving intellectual property disputes. In addition, negotiation, conciliation and mediation are some alternative forms of dispute resolution that can be chosen in the resolution of intellectual property disputes. The forms of mediation referred to here are voluntary mediation (out of court) and penal mediation in criminal charges.